Эволюционное развитие создания электронных звуков с помощью цифровых технологии - Абылова, Г. (SCIENCE and SOCIETY, 2020)
This article analyzes the evolution of electronic music via musical computer. The advantages of using composing music directly from a computer, creating electronic sounds via digital technologies are considered. The analysis of the development of electronic music are deliver with the help of great scientists contribution and their research in this direction.
Keywords: music; composition; computer; program; computer technology